ROLE OF SUNKIST PEELS EXTRACT AGAINST THE LEVEL OF ESTRADIOL AND MATURITY OF FOLLICLE IN THE FEMALE WISTAR RAT - MUTIA, MAYA SARI; SUHARTINA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The purpose of this study is to investigate the effect of Sunkist peel extract against the estradiol level and ovarian follicle in the female Wistar rats. Methods: This study was used 25 rats that were divided into five groups, namely, control (Na-CMC), standard (ethinylestradiol), and Sunkist peels extract-I, II, and III (300 mg/kg BW, 450 mg/kg BW, and 600 mg/kg BW). After 14 days, all rats were sacrificed by chloroform inhalation, and the ovarium was excised to histopathology preparation; meanwhile, the blood was collected for the serum. The histology and serum were determined the percentage of each type of follicle and the estradiol level, respectively. Results: The result of this study showed that increasing of the extract significantly increased not the level of estradiol level (p<0.05) but also the percentage of secondary and de Graaf follicle (p<0.05). Nevertheless, the percentage of primordial and primer follicle decreased, followed by increasing the extract dosage (p<0.05). Conclusion: It can be concluded that the Sunkist peels Sunkist peel increase both the level of estradiol serum and maturity of the follicle that increases the opportunity of female rats to be fertilized.